Hybrid composite actuator with shape retention capability for morphing flap of unmanned aerial vehicle (UAV). (1st July 2020) - Kim, Nam-Geuk; Han, Min-Woo; Iakovleva, Anna; Park, Hyung-Bin; Chu, Won-Shik; Ahn, Sung-Hoon
Abstract: A morphing flap is for changing the shape of wings continuously without any additional mechanical parts, which can reduce turbulence, aerodynamic drag, vibration, and noise versus the discontinuous geometry of 'conventional' flaps. Especially, smart materials based morphing technology can achieve various deformations without complex mechanical components, such as motors and joints. These characteristics are advantageous to reduce the operating cost of the aircraft through improvement of aerodynamic performance and weight saving. In this study, we designed a hybrid composite actuator capable of shape-retention, integrated with a shape memory polymer (SMP) scaffold and a shape memory alloy (SMA) wire. The hybrid composite actuator composed of SMP and SMA can maintain a deformed state without additional current to heat the SMA by using shape-memory effects of SMP. The measured maximum deformation angle of the actuator was 102° and the maintained angle was 70°. Then, the aerodynamic performance of the morphing flap was evaluated in wind-tunnel experiments. The morphing flap generated additional lift force during actuation and the lift-to-drag ratio of the morphing flap was higher than that of a conventional flap; the maximum difference was 81% at 10° of the angle of attack.